zmudz
  • zmudz
Given that \(x^n - (1/x^n)\) is expressible as a polynomial in \(x - (1/x)\) with real coefficients only if \(n\) is an odd positive integer, find \(P(z)\) so that \(P(x-(1/x)) = x^5 - (1/x)^5.\)
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
beginnersmind
  • beginnersmind
/cc
myininaya
  • myininaya
For some reason I first thought is to factor x^5-(1/x)^5
myininaya
  • myininaya
hmm I don't think I like that either I will continue to think

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

thomas5267
  • thomas5267
If that helps: \[ x^5\left(x^5-\frac{1}{x^5}\right)=x^{10}-1 \]
myininaya
  • myininaya
\[P(x-\frac{1}{x})=x^5-\frac{1}{x^5} \\ \text{ Let } z=x-\frac{1}{x} \\ zx=x^2-1 \\ x^2-zx-1=0 \\ x=\frac{ z \pm \sqrt{z^2+4}}{2} \\ P(z)=(\frac{z+\sqrt{z^2+4}}{2})^5-(\frac{2}{z+\sqrt{z^2+4}})^5\] I don't know which choice in x I should have made and P doesn't look like a polynomial but maybe it can be fix up I guess might be worth looking at what @thomas5267 said
thomas5267
  • thomas5267
\[ P(x)=x^5+ax^4+bx^3+cx^2+dx+e\\ \left(x-\frac{1}{x}\right)^5=x^5-5x^3+10x-10x^{-1}+5x^{-3}-x^{-5}\\ \left(x-\frac{1}{x}\right)^4=x^4-4x^2+6-4x^{-2}+x^{-4}\\ \left(x-\frac{1}{x}\right)^3=x^3-3x+3x^{-1}-x^{-3}\\ \left(x-\frac{1}{x}\right)^2=x^2-2+x^{-2}\\ x-\frac{1}{x}\\ \left(x-\frac{1}{x}\right)^5+a\left(x-\frac{1}{x}\right)^4+b\left(x-\frac{1}{x}\right)^3\\+c\left(x-\frac{1}{x}\right)^2+d\left(x-\frac{1}{x}\right)+e\\ =x^5+x^{-5}\\ a=0\\ b=5\\ c=0\\ d=5\\ e=0 \] Inelegant, but it works.

Looking for something else?

Not the answer you are looking for? Search for more explanations.